2021
DOI: 10.1111/apt.16563
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: radiomics for the diagnosis and prognosis of hepatocellular carcinoma

Abstract: Summary Background Advances in imaging technology have the potential to transform the early diagnosis and treatment of hepatocellular carcinoma (HCC) through quantitative image analysis. Computational “radiomic” techniques extract biomarker information from images which can be used to improve diagnosis and predict tumour biology. Aims To perform a systematic review on radiomic features in HCC diagnosis and prognosis, with a focus on reporting metrics and methodologic standardisation. Methods We performed a sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(40 citation statements)
references
References 101 publications
1
32
0
Order By: Relevance
“…There have been many liver cancer studies based on radiomics. However, these studies focused on the distinguishment of microvasculature and prediction of prognosis while may not meet the requirements for clinical application [ 29 ]. In this study, we established the model by analyzing the image features of patients and selected the features related to the pathological types of patients through logistic regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many liver cancer studies based on radiomics. However, these studies focused on the distinguishment of microvasculature and prediction of prognosis while may not meet the requirements for clinical application [ 29 ]. In this study, we established the model by analyzing the image features of patients and selected the features related to the pathological types of patients through logistic regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Second, in terms of scanning devices and parameters, both ours and Niu et al's study involved only 1 device (64-row CT) and the same tube voltage of 120Kv, whereas the other two studies involved 2 and more scanning devices and the tube voltage was not constant. Nonetheless, a recent systematic review 26 noted that no two studies can be directly compared with each other because proprietary feature extraction tools generate thousands of quantitative variables that have no meaning outside the context of individual studies, and suggested that standardization of protocols and outcome measures, sharing of algorithms and analysis methods, and external validation are necessary to avoid model heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…In studies on CT radiomics, automatic acquisition protocol and test-retest analysis have proven to be useful in overcoming the bias of acquisition protocols (Caruso et al, 2021). In light of the above limitations, radiomic models based on MRI are more difficult to reproduce across institutions than those based on CT images (Harding-Theobald et al, 2021). CT is recommended prior to TURBT according to the NCCN guidelines, and is still the most commonly used imaging method worldwide in diagnosing and staging BCa, mainly because CT is fast and inexpensive (Babjuk et al, 2019;Flaig et al, 2020).…”
Section: Discussionmentioning
confidence: 99%